Are circulating immune cells a determinant of pancreatic cancer risk? A prospective study using epigenetic cell count measures - Katzke, V; Le Cornet, C; Mahfouz, R; Brauer, B; Johnson, T; Canzian, F; Rebours, V; Boutron-Ruault, M-C; Severi, G; Schulze, MB; Olsen, A; Tjoenneland, A; et al. (American Association for Cancer Research, 2021)
Background: Evidence is accumulating that immune cells play a prominent role in pancreatic cancer etiology but prospective investigations are missing.